Evaluation of the effect of new generation denture base materials aged in artificial saliva at different pH levels on surface roughness and Candida albicans adhesion - Ezgi Arslan; Canan Akay; Demet Erdönmez; Esra Nur Avukat (BMC Oral Health)
Abstract Purpose The aim of this in vitro study was to evaluate the surface roughness and Candida albicans (C. albicans) biofilm formation of conventional heat-cured and different CAD/CAM milling denture base materials, after immersion in different pH levels of artificial saliva. Materials and methods Disc-shaped samples (10 × 2 mm) (n = 10) were prepared from two brands of CAD/CAM milled and conventional heat-cured PMMA denture base materials. The samples were immersed at 37 °C for 21 days in different pH levels of artificial saliva. The surface roughness (Ra) of each sample was measured using a contact profilometer before and after aging. C. albicans adhesion of the samples was determined using the Crystal Violet (CV) method. Results A significant increase in roughness was observed across all material groups maintained at pH 3 (P < 0.001). At pH 7, the roughness for heat-cured PMMA and G-PMMA groups increased significantly. Although pH 14 increased roughness in all groups, this was not significant. Upon comparison of roughness values post-aging, no significant differences were noted between the groups at pH 3 and pH 7; however, the G-PMMA group exhibited significantly lower surface roughness at pH 14 (P < 0.05). Among all material groups, the highest adhesion of C. albicans was observed in the heat-cured PMMA group. (P < 0.05). Conclusions Aging at different pH values caused surface changes in denture base materials and differences in C. albicans adhesion. Although there is an increase in surface roughness in all groups, these values are lower than the plaque accumulation threshold. The highest C. albicans adhesion was observed in heat-cured PMMA samples. Considering both roughness values and Candida adhesions, it is concluded that the new generation denture base materials are suitable for clinical use and should be widely used. Graphical Abstract